Usefulness of cerebrospinal fluid analysis in dogs and cats with suspected intracranial disease and normal magnetic resonance imaging - Monforte Monteiro, Susana R.; De Risio, Luisa; Alves, Lisa; Vanhaesebrouck, An E. (Frontiers in Veterinary Science, 2025)
Cerebrospinal fluid (CSF) analysis is a common diagnostic tool in the investigation of neurological presentations. Whether its routine use after every brain magnetic resonance imaging (MRI) is warranted is debated amongst clinicians, and its usefulness after a normal MRI has not yet been examined. To investigate whether CSF analysis affected the final diagnosis in dogs and cats with suspected intracranial disease in the presence of unremarkable magnetic resonance imaging (MRI), clinical, imaging and laboratory records of dogs and cats with suspected intracranial disease, unremarkable MRI and CSF analysis were reviewed in this multi-center retrospective study. Of 593 animals, (533 dogs and 60 cats), 17 dogs (3%) had abnormal CSF, nine of these demonstrating pleocytosis (with or without elevated microprotein) and eight showing hyperproteinorrachia alone. In only five of these dogs (0.8% of the total cohort) was the final diagnosis and/or treatment meaningfully affected by CSF findings: three diagnosed with inflammatory brain conditions and two had undetermined diagnoses, with corticosteroids initiated following abnormal CSF results. No cats in this population had an abnormal CSF. All dogs with a diagnosis based on abnormal CSF results had an abnormal neurological examination. In this population, CSF analysis was unlikely to reveal an undiagnosed intracranial condition following an unremarkable brain MRI, particularly in dogs presenting with a normal neurological examination. In dogs presenting with an abnormal neurological examination or a high suspicion of inflammatory disease, CSF evaluation following normal MRI is more likely to be diagnostically valuable.